A randomized, double blind, placebo controlled, split patch study to evaluate the effects of platelet rich plasma on alopecia areata - Khan, Bushra; Sharma, Ramesh; Borkar, Milind A. (International Journal of Research in Medical Sciences, 2018)
Background: Alopecia Areata is a T-cell–mediated autoimmune, often reversible disease in which the gradual loss of protection provided by immune privilege of the normal hair follicle plays an important role. It manifests as smooth, slightly erythematous (peach color) or normal-colored alopecic patches with short broken hair at the margins. It involves scalp most commonly, although other regions of body may be affected. Platelet rich plasma is an autologous concentration of platelets with a greater count in a small volume of plasma. Study aimed to evaluate the safety and efficacy of PRP therapy in Alopecia Areata. Methods: In this randomised, placebo controlled, split patch study, 30 patients of AA were recruited and injected with 1-1.5ml of autologous PRP made by double spin method into half the bald patch area and other half with placebo using insulin syringe once a month for 3 months. Outcome was assessed at the end of study by clinical photographs as regrowth of hair, dermoscopy findings as reduction in black dots, yellow dots and exclamation hair and Physician and patient self-assessment score. Results: Administration of autologous PRP has led to observable improvement in 20% case of PRP and only 3.3% of control cases. Decrease in number of dystrophic hair and hair regrowth with PRP was seen in 20% cases and in 17% patches. Conclusions: PRP in our setting was found to be minimally effective, but more efficacious than no treatment, and safe for AA patients.